Phylogeny and biogeography of the ephemeral Campsurus Eaton (Ephemeroptera, Polymitarcyidae) - Molineri, Carlos (2013)
To analyse speciation within the large Neotropical genus Campsurus Eaton, we examined apparent subgroupings by morphological methods using discrete and continuous character states. In this report, the albifilum group is redefined based on redescription of male imagos of Campsurus albifilum from the holotype and fresh material and from four closely related new species: Campsurus yavarin.sp. and C. fuliginatusn.sp. described from male imagos; and C. homaulosn.sp. and C. gracilipenisn.sp. described from imagos of both sexes. An illustrated key to distinguish the male adults of all species in the albifilum group is included. A phylogeny of the group is proposed based on a matrix of seven continuous and 12 discrete characters analysed under implied weights, and includes additional species representing all known or previously proposed groups. This demonstrates the practical application of methods using continuous characters to give additional resolution and support to the phylogeny. The monophyly of the major and the albifilum groups is confirmed. Based on these results, a biogeographical analysis is conducted (spatial analysis of vicariance) based on distributional records for each species. Two main vicariant events are found: (i) a west–east separation in tropical-subtropical South American lowlands, followed by (ii) a north–south separation of the Amazonas and Paraná regions. Sympatric speciation seems common: most sister species pairs are co-distributed, and show nonoverlapping ranges in body size.